PENGARUH MOTIVASI, ELECTRONIC WORLD OF MOUTH DAN LOKASI TERHADAP KEPUTUSAN BERKUNJUNG TAMAN SARIYOGYAKARTA - Patricia Cassita Eklesia (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2023)
This study aims to examine and discuss The Influence of Motivation, Electronic Word of Mouth and Location on Visit Decision to Taman Sari Yogyakarta. Thisresearch was conducted on 128 respondents with a quantitative descriptive approach and sampling techniques using purposive sampling. The data analysis used is statistical analysis in the form of SEM-PLS. The research results show that motivation has a positive and significant effect on visiting decisions. Electronic Word of Mouth has a positive and significant effect on visiting decisions. Location has positive and no significant effect on visiting decisions.